Mathematics in economics and business studies - Antanas Apynis; Eugenijus Stankus (Lietuvos Matematikos Rinkinys)
The books in microeconomics and macroeconomics are considered in view of mathematics consepts. The syllabus of mathematics for economics and business students is presented.